Effect of Pre-Sowing Seed Treatments on Seed Yield and Seed Quality Parameters in Ajwain [Trachyspermum ammi (L.)] - SS SAKHARE; AH RATHOD; MP WANKHADE; AM MISAL (Seed Research, 2026)
The present investigation, entitled “Effect of pre-sowing seed treatment on seed yield and seed quality parameters in Ajwain [Trachyspermum ammi (L.)]”, was carried out with the objectives to study the improved germination for better crop stand through pre sowing treatments. The experiment was conducted at Seed Technology Research Unit and laboratory of Department of Agricultural Botany, Vasantrao Naik Marathwada Krishi Vidyapeeth, Parbhani, Maharashtra, during Rabi, 2022–2023. A Randomised Block Design (RBD) with two replications was used to assess the experimental material. Two genotypes of Ajwain variety Local and AA-1-19 were sown and seven pre-sowing treatments GA3 (100 ppm), KNO3 (0.3%), T. asperilium (6g kg seeds single coat), T. harzianum (6g/kg seeds single coat), T. viride (6g/kg seeds single coat), Bavistin (2g/kg seeds) and Control were studied. Observations were recorded on following characters viz., field emergence (%), plant height (cm), number of umbel per plant, 1000 seed weight (g), seed yield per plant (g) and seed yield per plot (g). It was observed in the present study that the maximum field emergence was observed with treatment GA3 in both the varieties. The maximum plant height, maximum number of umbel per plant, maximum seed yield per plant, maximum 1000 seed weight, maximum seed yield per plot was noticed by seed treatment with (Trichoderma spp.) i.e T.harzianum.